Educational Gradients Behind Medical Adverse Event Deaths in the US—A Time Series Analysis of Nationwide Mortality Data 2010–2019 - Oura, Petteri (Frontiers in Public Health, 2022)
Background Deaths due to medical care appear common. Individuals with low socioeconomic position seem to be at a higher risk for sustaining a medical adverse event and premature death. This time series analysis aimed to assess educational gradients behind adverse event deaths in the US over the period 2010–2019. Methods Publicly available mortality and census data were retrieved from official sources. The data included age, sex, educational attainment, and underlying cause of death. Adverse event deaths were identified by ICD-10 codes Y40—Y84 and Y88. Four education categories were created in accordance with the International Standard Classification of Education 2011 coding scheme [No high school or General Educational Development (GED); High school or GED; Some college; Bachelor's degeree or higher]. To capture also highly educated individuals, the analysis was delimited to ≥30-year-olds. Age-adjusted mortality rates (AMRs) were compared between education categories by means of mortality plots and linear mixed models. Results A total of 25,897,334 certified deaths occurred among ≥30-year-olds during the study period. The underlying cause of death was an adverse event in a rarity of cases (0.12%, n = 31,997). Individuals with Bachelor's degeree or higher had the lowest adverse event AMRs (6.1–12.4 per million per year), followed by the Some college category (9.6–18.6), the High school or GED category (17.1–35.4), and finally the No high school or GED category (20.0–36.0). AMRs showed a gradual increase as education level decreased (p ≤ 0.001 against those with Bachelor's degeree or higher). Moreover, the temporal increase in adverse event AMRs was more pronounced among individuals with low than high education; the contrasts between categories were greatest toward the end of the study period. Conclusion The findings of this study suggest that the widening socioeconomic gradients in mortality extend also to fatal adverse events. Future studies should aim to analyze whether access to care, severity of the condition at presentation, quality of care, and social determinants of health may drive the gradients.